2009
DOI: 10.1299/jbse.4.500
|View full text |Cite
|
Sign up to set email alerts
|

Compressive Characteristics of Porcine Whole Liver

Abstract: The liver is one of the injury regions impacted by the steering wheel during a traffic accident. Therefore, in the field of impact biomechanics, the study of the liver has attracted considerable interest. We consider the case of abdominal compression by a steering wheel and perform quasi-static compression tests using a full-scale porcine liver that is not shaped into a cylinder or a cube in order to determine the basic mechanical properties of an unaltered liver. A human liver and a porcine liver have differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 8 publications
(7 reference statements)
1
1
0
Order By: Relevance
“…83 ± 4.32, 70.63 ± 4.32, 45.88 ± 2.83 and 22.33 ± 2.10 J m −2 ) with respectively increasing needle diameters (d = 2, 3, 4 and 5 mm), in other words with increasing contact areas (A C = 12.6, 28.3, 50.3 and 78.6 mm 2 ). Similar results can be seen from the indentation tests of Kaneta et al (2009) on whole porcine livers with a plate (l = 300 mm, b = 300 mm and h = 30 mm) and a cylindrical (d = 10 mm and h = 100 mm) indenter. One can note that only 2%-4% of the load required to initiate rupture of a liver lobe during indentation using the plate indenter (causing a square contact area of A C = 0.09 m 2 ) is required while using the cylindrical indenter (causing a circular contact area of A C = 7.86 × 10 −5 m 2 ).…”
Section: Introductionsupporting
confidence: 83%
See 1 more Smart Citation
“…83 ± 4.32, 70.63 ± 4.32, 45.88 ± 2.83 and 22.33 ± 2.10 J m −2 ) with respectively increasing needle diameters (d = 2, 3, 4 and 5 mm), in other words with increasing contact areas (A C = 12.6, 28.3, 50.3 and 78.6 mm 2 ). Similar results can be seen from the indentation tests of Kaneta et al (2009) on whole porcine livers with a plate (l = 300 mm, b = 300 mm and h = 30 mm) and a cylindrical (d = 10 mm and h = 100 mm) indenter. One can note that only 2%-4% of the load required to initiate rupture of a liver lobe during indentation using the plate indenter (causing a square contact area of A C = 0.09 m 2 ) is required while using the cylindrical indenter (causing a circular contact area of A C = 7.86 × 10 −5 m 2 ).…”
Section: Introductionsupporting
confidence: 83%
“…of different types of organs with different types of instruments. Some of the most relevant studies about the material and rupture behavior of intra-abdominal organs in the quasi-static regime (in vivo, in vitro as well as ex vivo) have been reported using needle insertion (Okamura et al 2004, Azar and Hayward 2008, Mahwash and Dupont 2010, Gokgol et al 2012), uniaxial compression (Farshad et al 1999and Snedeker et al 2005a, Kaneta et al 2009 and uniaxial tension tests (Brunon et al 2010, Kemper et al 2010, Kemper et al 2012, Untaroiu and Lu 2013. From needle insertion tests on whole bovine livers, Gokgol et al (2012) reported an almost linearly decreasing contact-area specific rupture work 7 of the livers (W AC = 110.…”
Section: Introductionmentioning
confidence: 99%